Impacts of extreme storm and flood events on coastal areas: Data from recent disasters in the Eastern Mediterranean region - Diakakis, Μ.,; Gogou, A.,; Filis, C.,; Mavroulis, S.,; Sarantopoulou, A.,; Kapris, I.,; Vassilakis, Emm.,; Katsetsiadou, K.-N.,; Kotsi, E.,; Spyrou, Ν.,; Konsolaki, A.,; Stamati, E.,; et al. (18th Plinius Conference on Mediterranean Risks, 2024)
The projected increase in frequency of flood extremes, attributed to climate change, poses a significant threat to coastal regions throughout the Mediterranean. Consequences encompass extensive geomorphological changes, infrastructural degradation, property damage, pollution of the aquatic environment, and other adverse socio-economic impacts, also threating the blue economy—a vital economic driver of the region. Acknowledging the pivotal role of coastal areas as critical nodes for both economic activities and ecologically valuable natural landscapes, it becomes imperative to deepen our understanding of the mechanisms and extents to which extreme flood events can impact these vulnerable coastal zones. This work focuses on exploring the impacts on the coastline of recent extreme storm events in the Eastern Mediterranean. The study aims to explore and classify the typology of effects, the severity of impacts and examine their spatial distribution as means to contribute to an improved understanding of extreme storm and flooding consequences in the region.